High-strength low-expansion microcrystalline glass material, preparation method and application thereof

CN118307219BActive Publication Date: 2026-10-27CNBM PHOTONICS TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410422522.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-09
Publication Date
2026-10-27
Estimated Expiration
2044-04-09

AI Technical Summary

Technical Problem

然而,据发明人研究发现,目前微晶玻璃即使经过化学强化也难以同时满足高强度和低膨胀的性能要求,从而难以用于制备原子钟的微波腔

Benefits of technology

[0043]本发明提供的一种高强度低膨胀微晶玻璃材料,具有优异的低膨胀系数,热膨胀系数(0±0.2)×10-7/℃,较小的应力,应力双折射≤6nm/cm,较好的光谱透过率,具有较好的内质,100cm3内直径>0.15mm的气泡个数为0,化学强化后具有较高的弯曲强度,弯曲强度≥200MPa。可用于制备原子钟的微波腔,在航空航天、空间跟踪、导航、射电天文、守时及频率计量等方面均起到重要的作用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118307219B_ABST
    Figure CN118307219B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of glass, and relates to a microcrystalline glass material, in particular to a high-strength low-expansion microcrystalline glass material and a preparation method and application thereof. The preparation method comprises a strengthening process of the microcrystalline glass, and the microcrystalline glass is subjected to at least two chemical strengthening; wherein the first chemical strengthening is performed in a salt bath of a sodium salt, and the second chemical strengthening is performed in a salt bath of a potassium salt or a mixed salt of the potassium salt and the sodium salt. The high-strength low-expansion microcrystalline glass material provided by the application has a low expansion coefficient, a small stress birefringence, and a high bending strength, and can be used for preparing a microwave cavity of a hydrogen atomic clock, and plays an important role in aviation, aerospace, space tracking, navigation, radio astronomy, time keeping and frequency measurement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of glass technology and relates to a microcrystalline glass material, specifically a high-strength, low-expansion microcrystalline glass material, its preparation method, and its application. Background Technology

[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

[0003] Hydrogen atomic clocks, with their excellent medium- and long-term stability, have important applications in long-baseline measurements, satellite navigation, deep space exploration, and metrology. The microwave cavity, as the core component of the hydrogen atomic clock, provides the environment for the interaction between the electromagnetic field and hydrogen atoms. Within the storage bubble of the microwave cavity, hydrogen atoms complete energy level transitions and emit microwave signals.

[0004] However, to meet the usage and performance requirements of atomic clocks, the glass material used in their microwave cavities must possess excellent low expansion properties, high resistance to temperature changes, high thermal stability, high mechanical strength, and ease of processing, and be able to operate stably in environments with large temperature variations. Currently, domestic technology generally uses quartz glass as the structural material for microwave cavities, and the overall performance and reliability of these systems still need improvement.

[0005] Glass-ceramics are glasses in which crystals have precipitated. Compared to glass without crystals, glass-ceramics are harder and less prone to damage. After chemical strengthening, glass-ceramics have a higher stress limit, enabling them to maintain high strength while preventing breakage. However, according to the inventors' research, even with chemical strengthening, it is currently difficult for glass-ceramics to simultaneously meet the performance requirements of high strength and low expansion, making it unsuitable for use in the fabrication of microwave cavities for atomic clocks.

[0006] The object of this invention is to overcome or improve at least one disadvantage of the prior art, or to provide a useful alternative. Unless the context clearly requires otherwise, the words “comprising” and “including” should be interpreted in an inclusive sense rather than an exclusive or exhaustive sense throughout the specification and claims; that is, in the sense of “including, but not limited to”. Summary of the Invention

[0007] To address the shortcomings of existing technologies, the present invention aims to provide a high-strength, low-expansion microcrystalline glass material, its preparation method, and its applications. The high-strength, low-expansion microcrystalline glass material provided by the present invention is a reinforced microcrystalline glass after microcrystalline glass strengthening treatment. This reinforced microcrystalline glass has a low coefficient of expansion, low stress birefringence, and high bending strength. It can be used to prepare the microwave cavity of a hydrogen atomic clock and plays an important role in aerospace, space tracking, navigation, radio astronomy, timekeeping, and frequency metrology.

[0008] To achieve the above objectives, the present invention provides the following technical solution:

[0009] In one aspect, a method for preparing a high-strength, low-expansion microcrystalline glass material includes a process of strengthening the microcrystalline glass.

[0010] The strengthening process is as follows: the microcrystalline glass is subjected to at least two chemical strengthening processes; wherein the first chemical strengthening is carried out in a sodium salt salt bath, and the second chemical strengthening is carried out in a potassium salt or a mixed salt of potassium and sodium salts.

[0011] The microcrystalline glass, by mass percentage, comprises: 50-60% SiO2, 15-25% Al2O3, 5-10% P2O5, 1-3% ZrO2, 1-3% TiO2, 0.5-2% MgO, 2-5% Li2O, 5.1-11% Na2O, 0-2% K2O, 0.5-2% ZnO, and 0.1-3% Sb2O3.

[0012] First, this invention utilizes microcrystalline glass in which:

[0013] SiO2 exists in the glass structure as [SiO4] tetrahedra, and its role in glass is to reduce the coefficient of thermal expansion and improve the glass's thermal stability, heat resistance, chemical stability, and mechanical strength. Al2O3 is an intermediate oxide in glass, and most of the Al in the glass structure is... 3+ Both can form a [AlO4] tetrahedral structure, and the volume of [AlO4] in glass is 41 cm³. 3 / mol, [SiO4] volume is 27cm³ 3 [AlO4] has a volume 52% larger than [SiO4], thus [AlO4] increases the glass porosity, which is beneficial for improving ion exchange efficiency and giving the glass material excellent chemical strengthening properties. However, excessive SiO2 and Al2O3 will inevitably lead to an increase in melting temperature and viscosity, placing a heavy burden on the glass melting and refining processes. Therefore, in the microcrystalline glass used in this invention, the SiO2 content ranges from 50% to 60%, and the Al2O3 content ranges from 15% to 25%.

[0014] P2O5, ZrO2, and TiO2 are optional nucleating agents. P2O5 exists in glass as [PO4], which contains one phosphorus-oxygen double bond (P=O), resulting in poor structural stability. It must be present in conjunction with Al2O3 or B2O3, along with a large amount of SiO2, to stabilize the glass structure. The introduction of TiO2 and ZrO2 not only effectively promotes nucleation but also refines the grain size, promoting the precipitation of nanoscale crystals in the glass-ceramic. Furthermore, ZrO2 helps improve the chemical stability and visible light transmittance of the glass. Therefore, in the glass-ceramic used in this invention, the content of P2O5 ranges from 5% to 10%, the content of ZrO2 ranges from 1% to 3%, and the content of TiO2 ranges from 1% to 3%.

[0015] Li₂O and Na₂O, as oxides in the glass network, can significantly reduce the glass melting temperature, improve melt quality, and enhance glass forming. However, excessively high content can affect the chemical stability of the glass and have a series of impacts on the forming process. Therefore, in the microcrystalline glass used in this invention, the content of Li₂O ranges from 2% to 5%, and the content of Na₂O ranges from 5.1% to 11%.

[0016] Sb₂O₃ is mainly used as a clarifying agent in glass. Its redox properties remove or reduce impurities in the glass, and it also inhibits bubble formation, thereby improving the transparency and purity of the glass. Therefore, in the microcrystalline glass used in this invention, the Sb₂O₃ content ranges from 0.1% to 3%.

[0017] In addition, the microcrystalline glass used in this invention also needs to contain 0.5-2% MgO, 0-2% K2O and 0.5-2% ZnO.

[0018] This invention employs at least two further chemical strengthening processes on the microcrystalline glass with the above-described composition. The first chemical strengthening primarily takes place in a sodium salt bath. During ion exchange, Li in the microcrystalline glass... + With Na in molten salt + Ion exchange, due to Li + With a relatively small radius, its ion diffusion coefficient is large, and its ion migration ability is strong, making it easy to diffuse from the interior of the glass into the molten salt. Na + Deeper penetration into the glass allows for the formation of a deep surface compressive stress layer within the microcrystalline glass, resulting in a greater depth of ion exchange (DOL). The second chemical strengthening process then takes place in a salt bath containing potassium salts or a mixture of potassium and sodium salts, producing Li... + with Na + In addition to ion exchange, Na+ was also produced. + With K + Ion exchange, due to K+ radius compared to Na + This increases the compressive stress (CS) on the glass surface by 35%, further enhancing it. Additionally, Li... + and Na + Ions are essential components for ion exchange. With the co-introduction of Li₂O and Na₂O, a two-step chemical strengthening method is employed, which facilitates the formation of a deeper ion exchange depth. This results in chemically strengthened glass-ceramics with higher surface compressive stress and a deeper ion exchange depth, leading to higher strength in the strengthened low-expansion glass-ceramics. Simultaneously, it exhibits a lower coefficient of expansion, lower stress birefringence, and lower bubble density.

[0019] The chemical strengthening described in this invention refers to placing the microcrystalline glass in a salt bath for single or multiple chemical ion exchanges. The salt bath used for ion exchange can be a lithium salt, sodium salt, potassium salt, or a mixture of these three molten salts. Further, the sodium salt used in the salt bath is sodium nitrate. Further, the potassium salt used in the salt bath is potassium nitrate.

[0020] In some embodiments, during the chemical enhancement process, the temperature during ion exchange is 380–600°C and the time is 60–600 min.

[0021] In one or more embodiments, during the first chemical strengthening process, the temperature during ion exchange is 380–600°C and the time is 60–600 min.

[0022] In one or more embodiments, during the second chemical enhancement process, the temperature during ion exchange is 380–580°C and the time is 60–600 min.

[0023] In some embodiments, the microcrystalline glass is chemically strengthened twice.

[0024] In some embodiments, a catalyst is added to the salt bath during the chemical enhancement process. The addition of the catalyst accelerates the chemical enhancement process. The catalyst may be, for example, KOH, KCl, K₂CO₃, Rb₂CO₃, KH₂PO₄, Ca(PO₃)₂, K₃PO₄, K₂SO₄, or a mixture thereof. Specifically, the mass of the added catalyst is 0–10 wt% of the total salt mass in the salt bath, for example, 1–10 wt%, 2–10 wt%, 3–10 wt%, 4–10 wt%, 5–10 wt%, 2–9 wt%, 3–9 wt%, 4–9 wt%, 5–9 wt%, 3–8 wt%, 4–8 wt%, 5–8 wt%, 3–7 wt%, 4–7 wt%, 5–7 wt%, 3–6 wt%, 4–6 wt%, 5–6 wt%, 4–5 wt%, etc.

[0025] Studies have shown that adding catalysts to different chemical strengthening processes affects the performance of the final product (i.e., high-strength, low-expansion glass-ceramic material). In some embodiments, a catalyst is added to the salt bath during the first chemical strengthening process. The catalyst content in the first chemical strengthening process is, for example, 1–10 wt%, 2–10 wt%, 3–10 wt%, 4–10 wt%, 5–10 wt%, 2–9 wt%, 3–9 wt%, 4–9 wt%, 5–9 wt%, 3–8 wt%, 4–8 wt%, 5–8 wt%, 3–7 wt%, 4–7 wt%, 5–7 wt%, 3–6 wt%, 4–6 wt%, 5–6 wt%, 4–5 wt%, etc.

[0026] In some embodiments, a catalyst is added to the salt bath during the second chemical enhancement process. The catalyst content in the first chemical enhancement process is, for example, 1–10 wt%, 2–10 wt%, 3–10 wt%, 4–10 wt%, 5–10 wt%, 2–9 wt%, 3–9 wt%, 4–9 wt%, 5–9 wt%, 3–8 wt%, 4–8 wt%, 5–8 wt%, 3–7 wt%, 4–7 wt%, 5–7 wt%, 3–6 wt%, 4–6 wt%, 5–6 wt%, 4–5 wt%, etc. Studies have shown that the catalyst content in the second chemical enhancement process affects the performance of the final product, with better performance observed at content levels of 3–7 wt%, 4–7 wt%, 5–7 wt%, 3–6 wt%, 4–6 wt%, 5–6 wt%, 4–5 wt%, etc.

[0027] In some embodiments, a catalyst is added to the salt bath in both chemical strengthening processes, and the catalyst content in the second chemical strengthening process is 3-6 wt%, preferably 4-5 wt%. Studies have shown that the final product produced under these conditions has better performance. The catalyst content in the first chemical strengthening process is 1-10 wt%. Examples of catalyst content in the first chemical strengthening process include 2-10 wt%, 3-10 wt%, 4-10 wt%, 5-10 wt%, 2-9 wt%, 3-9 wt%, 4-9 wt%, 5-9 wt%, 3-8 wt%, 4-8 wt%, 5-8 wt%, 3-7 wt%, 4-7 wt%, 5-7 wt%, 3-6 wt%, 4-6 wt%, and 5-6 wt%.

[0028] In some embodiments, the preparation method further includes a process for preparing microcrystalline glass.

[0029] In one or more embodiments, the preparation process is as follows: the raw materials are mixed evenly according to the composition ratio of the microcrystalline glass, and then melted, shaped, and annealed sequentially to obtain a glass blank. The glass blank is then microcrystallized. The raw materials used in this invention can be selected from the following materials as needed: quartz sand, aluminum hydroxide, phosphorus pentoxide, zirconium oxide, titanium oxide, magnesium oxide, lithium carbonate, sodium carbonate, potassium carbonate, zinc oxide, and antimony trioxide.

[0030] Specifically, the melting temperature is 1580–1660℃. After melting, mechanical stirring is used to assist in bubbling and clarification, which helps remove air bubbles from the molten glass. This not only improves the quality of the glass preform but also enhances the subsequent microcrystallization effect.

[0031] Specifically, the molding temperature is 1450–1530℃.

[0032] Specifically, the annealing temperature is 600–720℃.

[0033] Specifically, the temperature for microcrystallization is 520–850 °C.

[0034] More specifically, microcrystallization includes nucleation and crystallization. Nucleation is performed at 520–610°C for 1–5 hours. Crystallization is performed at 780–850°C for 3–7 hours.

[0035] Secondly, a high-strength, low-expansion microcrystalline glass material is obtained by the above-mentioned preparation method.

[0036] In some embodiments, the coefficient of thermal expansion under conditions of 0–50°C is (0 ± 0.2) × 10⁻⁶. -7 / ℃.

[0037] In some embodiments, the stress birefringence is 5–6 nm / cm.

[0038] In some embodiments, 100cm 3 The number of bubbles with an inner diameter greater than 0.15 mm is 0.

[0039] In some embodiments, the flexural strength is 200–228 MPa.

[0040] Thirdly, the application of the aforementioned high-strength, low-expansion microcrystalline glass material in the microwave cavity of an atomic clock.

[0041] Fourthly, an atomic clock whose microwave cavity is made of the aforementioned high-strength, low-expansion microcrystalline glass material.

[0042] The beneficial effects of this invention are as follows:

[0043] This invention provides a high-strength, low-expansion microcrystalline glass material with an excellent low coefficient of thermal expansion, specifically (0±0.2)×10⁻⁶. -7 / ℃, low stress, stress birefringence ≤6nm / cm, good spectral transmittance, good internal quality, 100cm 3 The number of bubbles with an inner diameter > 0.15 mm is 0. After chemical strengthening, it exhibits high flexural strength, ≥ 200 MPa. It can be used to fabricate microwave cavities for atomic clocks, playing an important role in aerospace, space tracking, navigation, radio astronomy, timekeeping, and frequency metrology. Attached Figure Description

[0044] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0045] Figure 1 The transmittance curve of the reinforced microcrystalline glass (5mm thickness) in Example 4 of the present invention is shown.

[0046] Figure 2 This is a comparison chart of the bending strength values ​​of the microcrystalline glass after chemical strengthening in Examples 1-5 and Comparative Examples 1-3 of the present invention.

[0047] Figure 3 The graph shows a comparison of the thermal expansion coefficient and stress birefringence values ​​of the microcrystalline glass strengthened in Examples 1-5 and Comparative Examples 1-3 of this invention. Detailed Implementation

[0048] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments and comparative examples.

[0049] Example 1

[0050] The microcrystalline glass of this embodiment is composed of the following components by mass percentage: 54.5% SiO2, 25.0% Al2O3, 5.0% P2O5, 1.0% ZrO2, 1.0% TiO2, 0.5% MgO, 2.0% Li2O, 5.1% Na2O, 1.0% K2O, 1.9% ZnO, and 3.0% Sb2O3.

[0051] Quartz sand, aluminum hydroxide, phosphorus pentoxide, zirconium oxide, titanium oxide, magnesium oxide, lithium carbonate, sodium carbonate, potassium carbonate, zinc oxide, and antimony trioxide are used as raw materials. They are mixed evenly according to the composition ratio of the microcrystalline glass described in this embodiment to prepare a batch material. The batch material is heated to 1660°C to melt, mechanically stirred to assist bubbling and clarification, and then cooled to 1515°C for manual casting. After molding, it is annealed at 700°C for 3 hours to obtain glass blank.

[0052] The glass blank is first nucleated at 520℃ for 3 hours, then crystallized at 780℃ for 5 hours, and then precision machined into a glass cylinder.

[0053] The glass cylinder was first placed in a salt bath of 95wt% sodium nitrate and 5wt% sodium carbonate at 600℃ for chemical ion exchange. After 240 minutes, it was placed in a salt bath of potassium nitrate at 580℃ for chemical ion exchange. After 300 minutes, the high-strength, low-expansion microcrystalline glass material was obtained.

[0054] Example 2

[0055] The microcrystalline glass of this embodiment is composed of the following components by mass percentage: 60.0% SiO2, 15.0% Al2O3, 5.5% P2O5, 1.5% ZrO2, 1.0% TiO2, 1.0% MgO, 3.0% Li2O, 8.9% Na2O, 2.0% K2O, 2.0% ZnO, and 0.1% Sb2O3.

[0056] Quartz sand, aluminum hydroxide, phosphorus pentoxide, zirconium oxide, titanium oxide, magnesium oxide, lithium carbonate, sodium carbonate, potassium carbonate, zinc oxide, and antimony trioxide were used as raw materials. They were mixed evenly according to the composition ratio of the microcrystalline glass described in this embodiment to prepare a batch material. The batch material was heated to 1599°C to melt, and mechanical stirring was used to assist in bubbling and clarification. Then, the temperature was lowered to 1493°C and manually cast into shape. After molding, the glass blank was annealed at 720°C for 3 hours to obtain the glass blank.

[0057] The glass blank is first nucleated at 560℃ for 5 hours, then crystallized at 820℃ for 7 hours, and then precision machined into a glass cylinder.

[0058] The glass cylinder was first placed in a sodium nitrate salt bath at 425°C for chemical ion exchange. After 60 minutes, it was placed in a salt bath of 95 wt% potassium nitrate and 5 wt% potassium hydroxide at 380°C for chemical ion exchange. After 600 minutes, a high-strength, low-expansion microcrystalline glass material was obtained.

[0059] Example 3

[0060] The microcrystalline glass of this embodiment is composed of the following components by mass percentage: 54.0% SiO2, 21.0% Al2O3, 8.0% P2O5, 1.5% ZrO2, 1.0% TiO2, 0.5% MgO, 2.0% Li2O, 6.0% Na2O, 2.0% K2O, 2.0% ZnO, and 2.0% Sb2O3.

[0061] Using quartz sand, aluminum hydroxide, phosphorus pentoxide, zirconium oxide, titanium oxide, magnesium oxide, lithium carbonate, sodium carbonate, potassium carbonate, zinc oxide, and antimony trioxide as raw materials, the mixture is prepared by uniformly mixing according to the composition ratio of the microcrystalline glass described in this embodiment. The mixture is heated to 1621°C to melt, mechanically stirred to assist bubbling and clarification, and then cooled to 1621°C for manual casting. After molding, it is annealed at 600°C for 3 hours to obtain glass blank.

[0062] The glass blank is first nucleated at 610℃ for 1 hour, then crystallized at 850℃ for 3 hours, and then precision machined into a glass cylinder.

[0063] The glass cylinder was first placed in a sodium nitrate salt bath at 380°C for chemical ion exchange for 600 minutes. Then, it was placed in a potassium nitrate salt bath at 580°C for chemical ion exchange for 60 minutes, and the high-strength, low-expansion microcrystalline glass material was obtained.

[0064] Example 4

[0065] The microcrystalline glass of this embodiment is composed of the following components by mass percentage: 52.0% SiO2, 18.0% Al2O3, 7.0% P2O5, 1.5% ZrO2, 3.0% TiO2, 2.0% MgO, 5.0% Li2O, 10.0% Na2O, 0.5% ZnO, and 1.0% Sb2O3.

[0066] Using quartz sand, aluminum hydroxide, phosphorus pentoxide, zirconium oxide, titanium oxide, magnesium oxide, lithium carbonate, sodium carbonate, zinc oxide, and antimony trioxide as raw materials, the mixture is prepared by uniformly mixing according to the composition ratio of the microcrystalline glass described in this embodiment. The mixture is heated to 1588°C to melt, mechanically stirred to assist bubbling and clarification, and then cooled to 1450°C for manual casting. After forming, it is annealed at 642°C for 3 hours to obtain glass blank.

[0067] The glass blank is first nucleated at 642℃ for 2 hours, then crystallized at 790℃ for 4 hours, and then precision machined into a glass cylinder.

[0068] The glass cylinder was first placed in a salt bath of 95wt% sodium nitrate and 15wt% potassium nitrate at 468℃ for chemical ion exchange. After 450 min, it was placed in a salt bath of 96wt% potassium nitrate and 4wt% potassium carbonate at 450℃ for chemical ion exchange. After 200 min, the high-strength, low-expansion microcrystalline glass material was obtained.

[0069] Example 5

[0070] The microcrystalline glass of this embodiment is composed of the following components by mass percentage: 50.0% SiO2, 16.5% Al2O3, 10.0% P2O5, 3.0% ZrO2, 2.0% TiO2, 1.0% MgO, 4.0% Li2O, 11.0% Na2O, 1.0% K2O, 1.0% ZnO and 0.5% Sb2O3.

[0071] Quartz sand, aluminum hydroxide, phosphorus pentoxide, zirconium oxide, titanium oxide, magnesium oxide, lithium carbonate, sodium carbonate, potassium carbonate, zinc oxide, and antimony trioxide are used as raw materials. They are mixed evenly according to the composition ratio of the microcrystalline glass described in this embodiment to prepare a batch material. The batch material is heated to 1580°C to melt, and mechanical stirring is used to assist bubbling and clarification. Then, the temperature is lowered to 1478°C and manually cast into shape. After molding, it is annealed at 666°C for 3 hours to obtain glass blank.

[0072] The glass blank is first nucleated at 540℃ for 5 hours, then crystallized at 830℃ for 7 hours, and then precision machined into a glass cylinder.

[0073] The glass cylinder was first placed in a salt bath of 90wt% sodium nitrate and 10wt% potassium nitrate at 543℃ for chemical ion exchange. After 120 minutes, it was placed in a salt bath of 93wt% potassium nitrate and 7wt% potassium sulfate at 510℃ for chemical ion exchange. After 400 minutes, the high-strength, low-expansion microcrystalline glass material was obtained.

[0074] Comparative Example 1

[0075] The microcrystalline glass of this comparative example is composed of the following components by mass percentage: 48.0% SiO2, 26.0% Al2O3, 3.0% P2O5, 4.0% TiO2, 3.0% MgO, 6.0% Li2O, 2.0% Na2O, 6.0% K2O, and 2.0% Sb2O3.

[0076] Quartz sand, aluminum hydroxide, phosphorus pentoxide, titanium oxide, magnesium oxide, lithium carbonate, sodium carbonate, potassium carbonate, and antimony trioxide were used as raw materials. They were mixed evenly according to the composition ratio of the microcrystalline glass described above in this comparative proportion to prepare a batch material. The batch material was heated to 1550℃ to melt, and mechanical stirring was used to assist in bubbling and clarification. Then, the temperature was lowered to 1425℃ and manually cast into shape. After molding, it was annealed at 560℃ for 3 hours to obtain glass blank.

[0077] The glass blank is first nucleated at 500℃ for 6 hours, then crystallized at 860℃ for 2 hours, and then precision machined into a glass cylinder.

[0078] The glass cylinder was first placed in a salt bath of 95wt% sodium nitrate and 15wt% potassium nitrate at 468℃ for chemical ion exchange. After 450 min, it was placed in a salt bath of 96wt% potassium nitrate and 4wt% potassium carbonate at 450℃ for chemical ion exchange. After 200 min, the reinforced microcrystalline glass material was obtained.

[0079] Comparative Example 2

[0080] The microcrystalline glass of this comparative example is the same as that of Example 4, and is composed of the following components by mass percentage: 52.0% SiO2, 18.0% Al2O3, 7.0% P2O5, 1.5% ZrO2, 3.0% TiO2, 2.0% MgO, 5.0% Li2O, 10.0% Na2O, 0.5% ZnO and 1.0% Sb2O3.

[0081] Quartz sand, aluminum hydroxide, phosphorus pentoxide, zirconium oxide, titanium oxide, magnesium oxide, lithium carbonate, sodium carbonate, zinc oxide, and antimony trioxide were used as raw materials. They were mixed evenly according to the composition ratio of the microcrystalline glass described above in this comparative example to prepare a batch material. The batch material was heated to 1588℃ to melt, and mechanical stirring was used to assist in bubbling and clarification. Then, the temperature was lowered to 1450℃ and manually cast into shape. After molding, it was annealed at 642℃ for 3 hours to obtain glass blank.

[0082] The glass blank is first nucleated at 642℃ for 2 hours, then crystallized at 790℃ for 4 hours, and then precision machined into a glass cylinder.

[0083] The glass cylinder is first placed in a sodium nitrate salt bath at 350°C for chemical ion exchange. After 660 minutes, the reinforced microcrystalline glass material is obtained.

[0084] Comparative Example 3

[0085] The microcrystalline glass of this comparative example is the same as that of Example 4, and is composed of the following components by mass percentage: 52.0% SiO2, 18.0% Al2O3, 7.0% P2O5, 1.5% ZrO2, 3.0% TiO2, 2.0% MgO, 5.0% Li2O, 10.0% Na2O, 0.5% ZnO and 1.0% Sb2O3.

[0086] Quartz sand, aluminum hydroxide, phosphorus pentoxide, zirconium oxide, titanium oxide, magnesium oxide, lithium carbonate, sodium carbonate, zinc oxide, and antimony trioxide were used as raw materials. They were mixed evenly according to the composition ratio of the microcrystalline glass described above in this comparative example to prepare a batch material. The batch material was heated to 1588℃ to melt, and mechanical stirring was used to assist in bubbling and clarification. Then, the temperature was lowered to 1450℃ and manually cast into shape. After molding, it was annealed at 642℃ for 3 hours to obtain glass blank.

[0087] The glass blank is first nucleated at 642℃ for 2 hours, then crystallized at 790℃ for 4 hours, and then precision machined into a glass cylinder.

[0088] The glass cylinder was first placed in a salt bath of 96wt% potassium nitrate and 4wt% potassium carbonate at 468℃ for chemical ion exchange. After 450 min, it was placed in a salt bath of 95wt% sodium nitrate and 15wt% potassium nitrate at 450℃ for chemical ion exchange. After 200 min, the reinforced microcrystalline glass material was obtained.

[0089] The coefficient of thermal expansion of glass samples was tested using a Netzsch DIL 402 thermal expansion meter according to GB / T 16535-2008. For sample preparation, the glass sample was polished into a cylindrical strip with a diameter of 5×50mm, and both ends were made parallel. The heating rate was set to 5℃ / min, and the data acquisition period was 20ms.

[0090] The transmittance of glass samples was determined using a Shimadzu UV-Vis spectrophotometer (UV-3600Plus) according to GB / T 7962.12-2010. The test wavelength range was 350–1000 nm. The glass samples tested had optically polished surfaces and a thickness of 5 mm.

[0091] The bubble content of glass samples was observed using a projector according to GB / T 5949-2014. The projector magnification was 10 to 100 times, and the accuracy of the micrometer drum on the worktable was 0.01 mm. The surface of the glass sample to be observed needed to be polished. The appropriate magnification was selected according to the size and density of the bubbles and gas lines to be measured.

[0092] The birefringence of the sample was tested using a polarizing stress meter with a measurement accuracy of not less than ±3 nm / cm in accordance with JC / T 185-2013(2017), and the birefringence value of the sample was determined by the maximum optical path difference per centimeter.

[0093] The bending strength of glass samples was determined using a three-point bending tester in accordance with GB / T 6569-2006. The sample dimensions were 3mm×4mm×40mm. The four long sides of the glass sample were optically polished, and the long edges were chamfered. No special treatment was required for the end surface of the test sample.

[0094] The composition, method parameters, and performance of the glass samples in Examples 1-5 and Comparative Examples 1-3 are shown in Tables 1, 2, and 3, respectively.

[0095] Table 1. Composition of glass samples from Examples 1-5 and Comparative Examples 1-3

[0096]

[0097] Table 2. Methods for preparing glass samples in Examples 1-5 and Comparative Examples 1-3.

[0098]

[0099]

[0100] Table 3. Performance test results of glass samples from Examples 1-5 and Comparative Examples 1-3.

[0101]

[0102] Table 3 shows that, compared with Example 4, when using other systems of microcrystalline glass for strengthening, even with the same chemical strengthening process, Comparative Example 1 exhibits a higher coefficient of thermal expansion and lower stress birefringence, bubble density, and flexural strength. Compared with Example 4, Comparative Example 2, using the microcrystalline glass system of the present invention, achieves a high-strength, low-expansion microcrystalline glass material with advantages such as a lower coefficient of thermal expansion, smaller stress birefringence, zero bubble density, and higher flexural strength through two-step chemical strengthening, meeting the requirements for preparing the microwave cavity of a hydrogen atomic clock. Compared with Example 4, Comparative Example 3, using the microcrystalline glass system of the present invention, even with the same two-step chemical strengthening process, achieves higher thermal expansion coefficient, lower stress birefringence, zero bubble density, and higher flexural strength. The strengthening process involves a first chemical strengthening using a salt bath primarily composed of sodium salts, followed by a second chemical strengthening using a salt bath primarily composed of potassium salts. This process simultaneously achieves advantages such as a lower coefficient of thermal expansion, lower stress birefringence, zero bubble content, and higher flexural strength. Examples 1-5 also exhibit these advantages. The main reason for this is that the secondary chemical strengthening process, using a salt bath primarily composed of sodium salts followed by a salt bath primarily composed of potassium salts, results in a chemically strengthened glass-ceramic with a higher surface compressive stress and a deeper ion exchange depth. Consequently, the strengthened low-expansion glass-ceramic exhibits higher strength while simultaneously possessing a lower coefficient of thermal expansion, lower stress birefringence, and lower bubble content.

[0103] In the chemical strengthening process of Examples 1-5, salts different from the main salt, such as KNO3, KOH, and K2CO3, can be added as catalysts to enhance the chemical strengthening process. In Examples 2 and 4, the addition of 4-5 wt% catalyst during the second chemical strengthening process resulted in glass materials with lower coefficients of thermal expansion and higher flexural strength. Furthermore, the addition of catalyst during the first chemical strengthening process can further significantly reduce the coefficient of thermal expansion of the glass material and further improve its flexural strength.

[0104] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. The application of a high-strength, low-expansion microcrystalline glass material in the microwave cavity of an atomic clock, characterized in that, The process of strengthening the microcrystalline glass material is as follows: the microcrystalline glass is subjected to at least two chemical strengthening processes; wherein, the first chemical strengthening is carried out in a sodium salt bath, and the second chemical strengthening is carried out in a potassium salt or a mixed salt of potassium and sodium salts. The microcrystalline glass, by mass percentage, comprises: 50-60% SiO2, 15-25% Al2O3, 5-10% P2O5, 1-3% ZrO2, 1-3% TiO2, 0.5-2% MgO, 2-5% Li2O, 5.1-11% Na2O, 0-2% K2O, 0.5-2% ZnO, and 0.1-3% Sb2O3; The coefficient of thermal expansion of the high-strength, low-expansion microcrystalline glass material described above is (0±0.2)×10⁻⁶ under conditions of 0~50℃. -7 / ℃; In the first chemical enhancement process, a catalyst is added to the salt bath; the catalyst content in the first chemical enhancement process is 1~10 wt%.

2. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 1 in the microwave cavity of an atomic clock, characterized in that, During the chemical fortification process, the temperature for ion exchange is 380~600 ℃ and the time is 60~600 min.

3. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 2 in the microwave cavity of an atomic clock, characterized in that, During the first chemical enhancement process, the temperature for ion exchange was 380~600 ℃ and the time was 60~600 min.

4. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 2 in the microwave cavity of an atomic clock, characterized in that, During the second chemical enhancement process, the temperature for ion exchange was 380~580 ℃ and the time was 60~600 min.

5. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 1 in the microwave cavity of an atomic clock, characterized in that, The microcrystalline glass is chemically strengthened twice; Alternatively, a catalyst can be added to the salt bath during the chemical fortification process.

6. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 1 in the microwave cavity of an atomic clock, characterized in that, In the second chemical fortification process, a catalyst is added to the salt bath.

7. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 6 in the microwave cavity of an atomic clock, characterized in that, The catalyst content in the second chemical enhancement process is 3-7 wt%.

8. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 6 in the microwave cavity of an atomic clock, characterized in that, The catalyst content in the second chemical enhancement process is 4-7 wt%.

9. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 6 in the microwave cavity of an atomic clock, characterized in that, The catalyst content in the second chemical enhancement process is 5-7 wt%.

10. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 6 in the microwave cavity of an atomic clock, characterized in that, The catalyst content in the second chemical enhancement process is 4-6 wt%.

11. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 6 in the microwave cavity of an atomic clock, characterized in that, The catalyst content in the second chemical enhancement process is 5-6 wt%.

12. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 1 in the microwave cavity of an atomic clock, characterized in that, In both chemical fortification processes, a catalyst was added to the salt bath, and the catalyst content was 3-6 wt% in the second chemical fortification process.

13. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 12 in the microwave cavity of an atomic clock, characterized in that, The catalyst content in the second chemical strengthening process is 4-5 wt%.

14. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 1 in the microwave cavity of an atomic clock, characterized in that, It also includes the preparation process of glass-ceramics.

15. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 14 in the microwave cavity of an atomic clock, characterized in that, The preparation process is as follows: after mixing the raw materials evenly according to the composition ratio of microcrystalline glass, they are melted, shaped and annealed in sequence to obtain glass blanks, and then the glass blanks are microcrystalline.

16. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 15 in the microwave cavity of an atomic clock, characterized in that, The melting temperature is 1580~1660 ℃.

17. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 15 in the microwave cavity of an atomic clock, characterized in that, The molding temperature is 1450~1530 ℃.

18. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 15 in the microwave cavity of an atomic clock, characterized in that, The annealing temperature is 600~720 ℃.

19. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 15 in the microwave cavity of an atomic clock, characterized in that, The temperature for microcrystallization is 520~850 ℃.

20. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 19 in the microwave cavity of an atomic clock, characterized in that, Microcrystallization includes nucleation and crystallization processes.

21. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 20 in the microwave cavity of an atomic clock, characterized in that, The nucleation treatment was carried out at a temperature of 520~610 ℃ for 1~5 h.

22. The application of the high-strength, low-expansion microcrystalline glass material as described in claim 20 in the microwave cavity of an atomic clock, characterized in that, The crystallization treatment temperature is 780~850 ℃, and the time is 3~7 h.

23. A high-strength, low-expansion microcrystalline glass material, characterized in that, The microcrystalline glass material is the high-strength, low-expansion microcrystalline glass material as defined in any of the applications described in claims 1 to 22.

24. The high-strength, low-expansion microcrystalline glass material as described in claim 23, characterized in that, The coefficient of thermal expansion under conditions of 0~50℃ is (0±0.2)×10. -7 / ℃; Alternatively, the stress birefringence is 5~6 nm / cm; Or, 100 cm 3 The number of bubbles with an inner diameter > 0.15 mm is 0; Alternatively, the bending strength is 200~228 MPa.

25. An atomic clock, characterized in that, The microwave cavity of the atomic clock is made of the high-strength, low-expansion microcrystalline glass material as described in claim 23 or 24.

Citation Information

Patent Citations

  • Ultra-low-expansion glass ceramic for laser gyro and preparation method thereof

    CN101538118A

  • Aluminum silicate glass for touch screen

    CN102092940A

  • Glass ceramic, electronic equipment and preparation method of glass ceramic

    CN113526872A

  • Composition for preparing low-expansion transparent microcrystalline glass, low-expansion transparent microcrystalline glass as well as preparation method and application of low-expansion transparent microcrystalline glass

    CN115745411A